A Qualitative Study on the Intercultural Educational Sensitivity of the Professors at the University of Malaga (Spain) - Pareja-de-Vicente, Dolores; Alcalá-del-Olmo-Fernández, María José; Santos-Villalba, María Jesús; Leiva-Olivencia, Juan José (IOAP-MPDI, 2021)
This paper deals with the intercultural sensitivity of professors of Educational Sciences at the University of Malaga (Spain). The methodological approach of the study was qualitative, and the research techniques for data collection were in-depth interviews. The main technique for analyzing the information was content analysis. The results of the study show that the majority of university teachers identify interculturality as a value and a pedagogical proposal of great importance. Thus, there is a need to promote intercultural competences and a critical view of culture. In conclusion, the study highlights the existence of difficulties in developing interculturality, which requires a change towards comprehensive training and education in values in the university context
Keywords: Educación intercultural; Intercultural skills; Intercultural attitudes; Teacher training; Values education; Educational inclusion